![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(x^3-5x^2+8x-4\)
= \(\left(x^3-x^2\right)-\left(4x^2-4x\right)+\left(4x-4\right)\)
= \(x^2\left(x-1\right)-4x\left(x-1\right)+4\left(x-1\right)\)
= \(\left(x-1\right)\left(x^2-4x+4\right)\)
= \(\left(x-1\right)\left(x-2\right)^2\)
b/ \(x^3-x^2+x-1\)
= \(\left(x^3-x^2\right)+\left(x-1\right)\)
= \(x^2\left(x-1\right)+\left(x-1\right)\)
= \(\left(x-1\right)\left(x^2+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) co sai de ko
b)x3-2x2+4x2-8x+3x-6=x2(x-2)+4x(x-2)+3(x-2)=(x-2)(x2+4x+3)=(x-2)(x+3)(x+1)
c)x3-2x2+2x2-4x-3x+6=x2(x-2)+2x(x-2)-3(x-2)=(x-2)(x2+2x-3)=(x-2)(x+3)(x-1)
d)x3-3x2+x2-3x-2x+6=x2(x-3)+x(x-3)-2(x-3)=(x-3)(x2+x-2)=(x-3)(x+2)(x-1)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.x2-9
= (x-3)(x+3)
2. -2x2+2x+12
= -2x2+6x-4x+12
= -2x(x+2)+6(x+2)
= (x+2)(-2x+6)
4. -2x2+2x+24
= -2x2+8x-6x+24
= -2x(x+3)+8(x+3)
= (x+3)(-2x+8)
6. x2-5x+4
= x2-4x-x+4
= x(x-1) -4(x-1)
= (x-1)(x-4)
8. x2-7x+6
= x2-6x-x+6
= x(x-1)-6(x-1)
= (x-1)(x-6)
9. x2+5x+4
= x2+4x+x+4
= x(x+1)+4(x+1)
=(x+1)(x+4)
10. x2+7x+6
= x2 +x+6x+6
= x(x+1)+6(x+1)
= (x+6)(x+1)
K nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\left(x-2\right)^2-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2=15\)\(\Leftrightarrow x^3-6x^2+12x-8-x^3+27+6\left(x^2+2x+1\right)=15\)\(\Leftrightarrow-6x^2+12x+19+6x^2+12x+6=15\)
\(\Leftrightarrow24x=-10\)
\(\Leftrightarrow x=-\dfrac{5}{12}\)
Vậy:....
\(b,\left(5x+1\right)^2-\left(5x+3\right)\left(5x-3\right)=30\)
\(\Leftrightarrow25x^2+10x+1-25^2+9=30\)
\(\Leftrightarrow10x=20\)
\(\Rightarrow x=2\)
Vậy :....
\(c,\left(x+3\right)\left(x^2-3x+9\right)-x\left(x-2\right)\left(x+2\right)=15\)\(\Leftrightarrow x^3+27-x\left(x^2-4\right)=15\)
\(\Leftrightarrow x^3+27-x^3+4x=15\)
\(\Leftrightarrow4x=15-27=-12\)
\(\Leftrightarrow x=-3\)
vậy : .....
![](https://rs.olm.vn/images/avt/0.png?1311)
\(Q=\)\(1+\frac{x+3}{x^2+5x+6}:\left(\frac{8x^2}{4x^3-8x^2}-\frac{3x}{3x^2-12}-\frac{1}{x+2}\right)\)
\(Q=1+\frac{x+3}{x^2+3x+2x+6}:\left[\frac{8x^2}{4x^2\left(x-2\right)}-\frac{3x}{3\left(x^2-4\right)}+\frac{x-2}{\left(x+2\right)\left(x-2\right)}\right]\)
\(Q=1+\frac{x+3}{\left(x+3\right)\left(x+2\right)}:\left[\frac{2}{x-2}-\frac{x}{\left(x-2\right)\left(x+2\right)}+\frac{x-2}{\left(x+2\right)\left(x-2\right)}\right]\)
\(Q=1+\frac{1}{x+2}:\left[\frac{2\left(x+2\right)}{\left(x-2\right)\left(x+2\right)}-\frac{x+x-2}{\left(x-2\right)\left(x+2\right)}\right]\)
\(Q=1+\frac{1}{x+2}:\left[\frac{2x+4-2x+2}{\left(x-2\right)\left(x+2\right)}\right]\)
\(Q=1+\frac{1}{x+2}:\frac{6}{\left(x-2\right)\left(x+2\right)}\)
\(Q=1+\frac{1}{x+2}.\frac{\left(x-2\right)\left(x+2\right)}{6}\)
\(Q=1+\frac{x-2}{6}\)
\(Q=\frac{6+x-2}{6}\)
\(Q=\frac{x+4}{6}\)
b) khi \(Q=0\)thì \(\frac{x+4}{6}=0\)
\(\Rightarrow x+4=0\)
\(\Rightarrow x=-4\)
vậy \(x=-4\)khi \(Q=0\)
c) khi \(Q>0\)thì \(\frac{x+4}{6}>0\)
\(\Rightarrow x+4>0\)
\(\Leftrightarrow x>-4\)
vậy \(x>-4\)thì \(Q>0\)
\(3\left(x-1\right)^2-5x\left(x-6\right)=3\)
\(\Leftrightarrow3x^2-6x+3-5x^2+30x=3\)
\(\Leftrightarrow-2x^2+24x=0\Leftrightarrow2x\left(x-12\right)=0\)
\(\Leftrightarrow x=0,x=12\)